Nutraceutical Intervention Improves Older Adults' Cognitive Functioning - Small, Brent J. (Mary Ann Liebert, Inc., 2014)
Interventions to improve the cognitive health of older adults are of critical importance. In the current study, we conducted a double-blind, placebo-controlled clinical trial using a pill-based nutraceutical (NT-020) that contained a proprietary formulation of blueberry, carnosine, green tea, vitamin D3, and Biovin to evaluate the impact on changes in multiple domains of cognitive functioning. One hundred and five cognitively intact adults aged 65–85 years of age (M=73.6 years) were randomized to receive NT-020 (n=52) or a placebo (n=53). Participants were tested with a battery of cognitive performance tests that were classified into six broad domains—episodic memory, processing speed, verbal ability, working memory, executive functioning, and complex speed at baseline and 2 months later. The results indicated that persons taking NT-020 improved significantly on two measures of processing speed across the 2-month test period in contrast to persons on the placebo whose performance did not change. None of the other cognitive ability measures were related to intervention group. The results also indicated that the NT-020 was well tolerated by older adults, and the presence of adverse events or symptoms did not differ between the NT-020 and placebo groups. Overall, the results of the current study were promising and suggest the potential for interventions like these to improve the cognitive health of older adults.